SYMBOLIC ANALYSIS OF ELECTRONIC CIRCUITS USING WAVELET TRANSFORM - Al-Itaby, A. A.; Al-Naima, Prof. F. M.; Al-Itaby, A. A.; Al-Naima, Prof. F. M. (Iraqi Journal for Electrical and Electronic Engineering, 2007)
In recent years, symbolic analysis has become a well-established technique in circuit analysis and design. The symbolic expression of network characteristics offers convenience for frequency response analysis, sensitivity computation, and fault diagnosis. The aim of the paper is to present a method for symbolic analysis that depends on the use of the wavelet transform (WT) as a tool to accelerate the solution of the problem as compared with the numerical interpolation method that is based on the use of the fast Fourier transform (FFT).